Composition of Java-based router elements and its application to generalized video multicast. - Yu Dong (IEEE Network : the magazine of global information exchange)
We describe a software router capable of flexible service composition through plug and play of specialized Java software modules. These Java modules - previously developed for network simulation in the J-Sim project - are leveraged for actual deployment on our router through a JSocket class of objects. Our system provides significant software engineering benefits of simplified code development and safe composition/reuse of various router components. These benefits have proved highly useful in implementing new network services for emerging application needs. In particular, we present a paradigm of generalized multicast with application to large-scale video streaming. We detail the performance of our prototype implementation in terms of efficiency (when compared to a native C implementation) and its ability to satisfy the dynamic resource capabilities of a heterogeneous set of receiver end systems, including mobile handheld devices.